Pemodelan Proses Pemilihan Rute pada Protokol Babel dengan Activity Diagram dan Transition System - Ayu, Vittalis (Media Teknika, 2017)
Babel Routing Protocol was designed by Juliuz Chrobozcek and its written specification was published in RFC 6126 in April 2014. Babel is one of distance vector routing protocols that has its own distinctive features. Although it sends updates periodically to its neighbours, it also sends triggered updates whenever it detects its neighbour’s changes. The changes can include broken links and new link detections. Babel route selection process is also unique, because there are feasibility condition requirements to ensure that the routing loop does not exist during the routing process. Unified Modelling Language (UML) is a modelling language widely used in software engineering. Its popularity is based on its capability to express and describe different aspects of a software. Activity diagram is one of the UML models to describe the flow activity of a software execution. It answers and explains situations like the different states that the flow can reach and the prerequisite to reach the next states. On the other hand, transition systems describe the transition state of the running software. When a software is executed, we have to keep track of the state of the software. We need to describe how state can jump from one to anotherstate and what requirements to do the transition from one state to another one.It will be helpful inthe debugging process laterwhen some errors occur. However, the transition system can be derived from the activity diagram that has described the software flow. This researchis conducted to give more understanding about the flow of the route selection process in Babel Routing Protocol and describe the flow in the activity diagram and further define it with a transition system.